Adherence to treatment: what is done in Sweden? Practice, education and research - Södergård B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objective: The objective of this review was to identify the practice, education and research of pharmacists in Sweden in regard to adherence to treatment.Methods: Medline was searched up to the end of February 2008. In addition to the Medline search performed, other available sources were also used to identify relevant articles.Results: No adherence-specific programs have been implemented in Swedish pharmacies. No adherence-specific courses are provided in Swedish Universities educating pharmacists. The adherence-related research has so far mainly focused on refill non-adherence, primary non-adherence and patient reported non-adherence and readiness to treatment. Conclusions: Adherence-related practice and education of pharmacists will probably change due to the deregulation of the pharmacy market that will take place in the near future in Sweden. Research on adherence will need to be strengthened in the sense that it has so far not been guided by adherence-related theoretical frameworks, despite the fact that there are several theories to hand that try to explain adherence.